Anxiety Changes Depersonalization and Derealization Symptoms in Vestibular Patients. (28th January 2014) - Kolev, Ognyan I.; Georgieva-Zhostova, Spaska O.; Berthoz, Alain
Abstract : Background. Depersonalization and derealization are common symptoms reported in the general population. Objective. The aim of the present study was to establish the relationship between anxiety and depersonalization and derealization symptoms in patients with peripheral vestibular disorders. Methods. Twenty-four vestibular patients with anxiety and 18 vestibular patients without anxiety were examined for depersonalization and derealization symptoms. They were also compared to healthy controls. Results. The results revealed that anxiety consistently changes depersonalization and derealization symptoms in vestibular patients. They are more frequent, more severe, and qualitatively different in vestibular patients with anxiety than in those without anxiety. Conclusion. Anxiety has an effect on depersonalization and derealization symptoms in vestibular patients. The various hypotheses about the underlying mechanism of this effect were discussed.